Effects of Polarization Reversal on the Pitch Angle Scattering of Radiation Belt Electrons and Ring Current Protons by EMIC Waves. Issue 17 (5th September 2020) - Cao, Xing; Ni, Binbin; Summers, Danny; Shprits, Yuri Y.; Lou, Yuequn
Abstract: In this study, we investigate the effects of polarization reversal of electromagnetic ion cyclotron (EMIC) waves at the crossover frequencies on computations of bounce‐averaged pitch angle diffusion coefficients of radiation belt electrons and ring current protons. We find that inclusion of polarization reversal can cause significant changes of H + band‐induced particle diffusion coefficients, while scattering by the He + band is almost unaffected. Our results show that the pure L‐mode approach, which has been widely implemented in previous studies, tends to underestimate the diffusion coefficients of ultrarelativistic (>4 MeV) electrons and overestimate those of 10–50 and >100 keV protons caused by H + band EMIC waves. Especially for >100 keV protons, the differences in diffusion coefficients can be larger by an order of magnitude. We confirm that the polarization reversal can contribute importantly to the scattering loss of radiation belt electrons and ring current protons by H + band EMIC waves. Key Points: The effects of polarization reversal at the crossover frequencies on the particle scattering by EMIC waves are investigated While polarization reversal causes obvious changes in H + band‐induced scattering rates, scattering by the He + band is almost unaffected Polarization reversal of H + band increases the scattering rates of >4 MeV electrons and decreases those of 10–50 and >100 keV protons